1995
DOI: 10.3758/bf03214411
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mimicking of reaction time data: Single-process models, parameter variability, and mixtures

Abstract: Statistical mimicking issues involving reaction time measures are introduced and discussed in this article. Often, discussions of mimicking have concerned the question of the serial versus parallel processing of inputs to the cognitive system. Wewill demonstrate that there are several alternative structures that mimic various existing models in the literature. In particular, single-process models have been neglected in this area. When parameter variability is incorporated into single-process models, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 79 publications
1
129
0
Order By: Relevance
“…Logan (1992, Appendix B) showed that the Weibull closely mimicked the ex-Gaussian distribution (a convolution of a normal distribution and an exponential distribution) that provides an excellent approximation to observed reaction time distributions (Ratcliff & Murdock, 1976). Van Zandt and Ratcliff (1995) showed that the Weibull closely mimicked a mixture of gamma distributions. Moreover, a mixture of gammas chosen in the right way could approximate the power function reduction in the scale of the distribution with practice that is characteristic of the Weibull.…”
Section: Asymptotic Distributions Are Distributions Of Transformed Scmentioning
confidence: 99%
“…Logan (1992, Appendix B) showed that the Weibull closely mimicked the ex-Gaussian distribution (a convolution of a normal distribution and an exponential distribution) that provides an excellent approximation to observed reaction time distributions (Ratcliff & Murdock, 1976). Van Zandt and Ratcliff (1995) showed that the Weibull closely mimicked a mixture of gamma distributions. Moreover, a mixture of gammas chosen in the right way could approximate the power function reduction in the scale of the distribution with practice that is characteristic of the Weibull.…”
Section: Asymptotic Distributions Are Distributions Of Transformed Scmentioning
confidence: 99%
“…One technique, developed by Ashby and Townsend (1980) and Roberts and Sternberg (1992), is a test of whether two factors selectively influence processes whose durations are combined by addition to form the response time. For a critical analysis, see Van Zandt and Ratcliff (1995). A generalization of this technique is presented in Dzhafarov and Schweickert (1995), Dzhafarov and Cortese (1996), and Cortese and Dzhafarov (1996).…”
Section: Figmentioning
confidence: 99%
“…All process durations were sampled from gamma distributions (Van Zandt & Ratcliff, 1995), the shape and scale of which were calibrated from the data (more details are provided in the following calibration section below).…”
Section: Structure Of the Architecturementioning
confidence: 99%